The given equation can be written as, "\\left(D^{2}+4\\right) y=t^{2}+6e^{t}". The auxiliary equation is, "m^{2}+4=0". Solving, we get "m=\\pm 2i". The complementary function is,
"C.F=c_{1} \\cos (2 t)+c_{2} \\sin (2 t)." The particular integral is given by,
"\\begin{aligned}\nP.I &=\\frac{1}{D^{2}+4}\\left(t^{2}+6 e^{t}\\right) \\\\\n&=\\frac{1}{D^{2}+4} \\cdot t^{2}+\\frac{1}{D^{2}+4} \\cdot 6 e^{t} \\\\\n&=\\frac{1}{4}\\left(1+\\frac{D^{2}}{4}\\right)^{-1} \\cdot t^{2}+\\frac{6 e^{t}}{5} \\\\\n&=\\frac{1}{4}\\left(1-\\frac{D^{2}}{4}+\\cdots\\right) \\cdot t^{2}+\\frac{6 e^{t}}{5} \\\\\n&=\\frac{1}{4}\\left(t^{2}-\\frac{1}{2}\\right)+\\frac{6 e^{t}}{5} \\\\\n&=\\frac{t^{2}}{4}+\\frac{6 e^{t}}{5}-\\frac{1}{8}\n\\end{aligned}"
The general solution is, "\\displaystyle y=c_{1} \\cos (2 t)+c_{2} \\sin (2 t)+\\frac{t^{2}}{4}+\\frac{6 e^{t}}{5}-\\frac{1}{8}".
Hence, "\\displaystyle y'=-2 c_{1} \\sin (2 t)+2 c_{2} \\cos (2 t)+\\frac{t}{2}+\\frac{6 e^{t}}{5}" .
Given the initial conditions, "y(0)=0, y^{\\prime}(0)=5". Using the initial conditions we get,
"\\begin{aligned}\n\\displaystyle y(0) & = c_{1} +\\frac{6 }{5}-\\frac{1}{8}\\\\\n0&=c_{1} +\\frac{6 }{5}-\\frac{1}{8}\\\\\nc_{1}&=-\\frac{43}{40}\n\\end{aligned}"
"\\begin{aligned}\n\\displaystyle y'(0) & = 2c_{2} +\\frac{6 }{5}\\\\\n5&=2c_{2} +\\frac{6}{5}\\\\\n2c_{2}&= 5-\\frac{6}{5}\\\\\nc_{2}&=\\frac{19}{10}\n\\end{aligned}"
Hence, the general solution is,
"\\begin{aligned}\ny&=\\frac{19}{10} \\sin (2 t)-\\frac{43}{40} \\cos (2 t)+\\frac{t^{2}}{4}+\\frac{6 e^{t}}{5}-\\frac{1}{8}\\\\\ny&=\\frac{1}{40}\\bigg(76 \\sin (2 t)-43 \\cos (2 t)+10 t^{2}+48 e^{t}-5\\bigg)\n\\end{aligned}"
Comments
Leave a comment